Effects of different extracting conditions on anti-tyrosinase and antioxidant activities of Schizophyllum commune fruit bodies. (May 2019) - Abd Razak, Dang Lelamurni; Mohd Fadzil, Noor Hasni; Jamaluddin, Anisah; Abd Rashid, Nur Yuhasliza; Sani, Nor Ajila; Abdul Manan, Musaalbakri
Abstract: A current trend in cosmetic and cosmeceutical science is the search for edible ingredients with effective skin-repairing actives. Schizophyllum commune is a cultivated edible mushroom known to contain compounds that possess potent biological properties beneficial to skin health. However, research on the development of locally cultivated S. commune as a cosmeceutical ingredient is lacking. The objective of this preliminary study was to evaluate the effect of extraction conditions on the cosmeceutical properties of S. commune extract. Fruit bodies were extracted using two different temperatures; 4 °C and 30 °C at three different extraction times; 1, 12 and 24 h, using water as extracting solvent. Anti-pigmentation activity measured by a tyrosinase inhibition assay, as well as antioxidant activities, were evaluated. Biological components such as total phenolic, polysaccharide, and glucan content were also assessed. The results revealed that a 1 h extraction time at 4 °C or 30 °C produced extracts with the strongest anti-pigmentation effect, with the value of 94.2 and 95.4% respectively. At 4 °C, shorter extraction time yielded better ferric-reducing and DPPH-radical scavenging antioxidant activities, while results were varied at 30 °C. Based on our results, the optimal conditions for effective cosmeceutical properties in S. commune extract was extraction at 30 °C for 1 h. Further research on optimization of the extraction method and in-vitro efficacy test using cell lines should be commenced to thoroughly explore the potential of these mushroom extracts as cosmeceutical agents. Highlights: We use Schizophyllum commune fruitbodies in the extraction study We use different temperature (4 °C and 30 °C) and time (1, 12 and 24 h) settings We examine biological components and cosmeceutical-related biological activities of extracts Shorter extraction time produced extract with the best tyrosinase inhibition activity Extraction at 30 °C mostly yielded extracts with better antioxidant activities than extraction at 4 °C.